Approaches to Abuse of Dominance in EU Competition Law: Lesson Learned and Consumer Protection - Yorgita Pascallanda; Joy Andrea Sihombing (Business and Human Rights Law & Policy, 2025)
Competition law has several main objectives, which are: economic welfare, economic efficiency, and free and fair competition. Among such objectives, economic efficiency exists when available resources are allocated to their best use and the goods and services are distributed to individuals who appreciate them the most. For consumers, this leads to lower prices, higher quality of goods and service, and wider choices in the market, and increased innovation. By deterring anti-competitive conduct, competition law helps ensure that consumers are protected from conducts that may harm them. EU competition law has undergone significant changes to maintain competitive markets. The EU’s initial approach to abuse of dominant position focused more on the form of the undertakings’ conduct (form-based), which only assessed an action based on its form. This form-based approach is risky in producing false positives, that is, the wrong conclusion that an action is considered detrimental, when in practice, it may not actually be detrimental to competition or consumers. in applying Article 102 of the Treaty on the Functioning of the European Union (TFEU). In this regard, the Commission published a Discussion Paper indicating that the Commission planned to update its approach to Article 102 TFEU in 2005. This article will critically analyse the Guidance, its revision, and the changes between them to determine whether these concerns are justified or simply unfounded. It begins with an introduction and explores the prohibition of abuse of dominant position under Article 102 TFEU. It then continues with a discussion of the Guidance and its revisions and continues with key changes in the amending communication. An analysis of the changes will be provided, and followed by lessons, notably for Indonesia on ways to improve its enforcement of abuse of dominance to protect consumers’ interest.